Endovascular Treatment of Blunt Aortic Trauma: First Colombian Case Series - Hernán Yair Flórez de Moya; Alvaro Andrés Montenegro-Apraez; Laureano Ricardo Quintero Barrera; William Escobar Rojas; Luis David Perafan Fernandez; Santiago Serna Trejos (Journal of Endovascular Resuscitation and Trauma Management)
Background: Endovascular repair of the aorta has been established as the treatment of choice for patients with closed traumatic aortic injury, and its implementation has resulted in better clinical outcomes for patients. Our objective was to describe a case series of patients with closed traumatic aortic injury who received endovascular management. Methods: We carried out a retrospective review of the experience accumulated over 5 years in a level IV center in Colombia of the management of closed traumatic aortic injury with endovascular treatment. We found four patients with different aortic injuries described as grade II or III. Endovascular management was performed during the first 48 hours after admission to the emergency room; hospital survival was 100%, and there was no record of complications after the procedure. Conclusions: Endovascular repair is the treatment of choice for closed traumatic aortic injury, including scenarios of hemodynamic instability. This is the first case series published from Colombia.